Overcoming Limitations of Cisplatin Therapy by Additional Treatment With the HSP90 Inhibitor Onalespib - Mortensen, Anja Charlotte Lundgren; Mohajershojai, Tabassom; Hariri, Mehran; Pettersson, Marika; Spiegelberg, Diana (Frontiers in Oncology, 2020)
Rational Cisplatin based cancer therapy is an affordable and effective standard therapy for several solid cancers, including lung, ovarian and head and neck cancers. However, the clinical use of cisplatin is routinely limited by the development of drug resistance and subsequent therapeutic failure. Therefore, methods of circumventing cisplatin resistance have the potential to increase therapeutic efficiency and dramatically increase overall survival. Cisplatin resistance can be mediated by alterations to the DNA damage response, where multiple components of the repair machinery have been described to be client proteins of HSP90. In the present study, we have investigated whether therapy with the novel HSP90 inhibitor onalespib can potentiate the efficacy of cisplatin and potentially reverse cisplatin resistance in ovarian and head and neck cancer cells. Methods Cell viability, cancer cell proliferation and migration capacity were evaluated in vitro on models of ovarian and head and neck cancer cells. Western blotting was used to assess the downregulation of HSP90 client proteins and alterations in downstream signaling proteins after exposure to cisplatin and/or onalespib. Induction of apoptosis and DNA damage response were evaluated in both monotherapy and combination therapy groups. Results Results demonstrate that onalespib enhances the efficiency of cisplatin in a dose-dependent manner. Tumor cells treated with both drugs displayed lower viability and a decreased migration rate compared to vehicle-control cells and cells treated with individual compounds. An increase of DNA double strand breaks was observed in both cisplatin and onalespib treated cells. The damage was highest and most persistent in the combination group, delaying the DNA repair machinery. Further, the cisplatin and onalespib co-treated cells had greater apoptotic activity compared to controls. Conclusion The results of this study demonstrate that the reduced therapeutic efficacy of cisplatin due to drug-resistance could be overcome by combination treatment with onalespib. We speculate that the increased apoptotic signaling, DNA damage as well as the downregulation of HSP90 client proteins are important mechanisms promoting increased sensitivity to cisplatin treatment.